FTIR spectroscopy for adulterated drug analysis - Bunaciu, Andrei A. (Henry Stewart Talks, 2025)
FTIR spectroscopy in adulterated drugs, Adulterated products and counterfeit pharmaceuticals, Infrared spectroscopy, Detection of adulterated products, Adulterated drug analysis using IR spectroscopy, Sildenafil (Viagra), paracetamol and sibutramine, Herbal medicine, Dextrose, Kajal and Radix astragali